Generation of two iPSC lines (MHHi001-A-12 and MHHi001-A-13) carrying biallelic truncating mutations at the 3′-end of SRCAP using CRISPR/Cas9 - J. Rhode; L. Hagenau; J. Beimdiek; R. Ullmann; F. Hossain; A. Tzvetkova; L.R. Jensen; A.W. Kuss (Stem Cell Research, 2023)
Non-Floating Harbour Syndrome (FLHS) neurodevelopmental disorder (NDD) is a recently described disorder caused by mutations in certain regions of the SRCAP gene. We generated two iPSC lines that contain truncating mutation on both alleles at the 3′-end of SRCAP using CRISPR/Cas9 technology. Both cell lines are pluripotent, differentiate into the 3 germ layers and contain no genomic aberrations or off-target modifications. The cell lines form part of a human disease model to investigate the effects of truncating mutations in different regions of SRCAP.